Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1136/jech-2019-212699
|View full text |Cite
|
Sign up to set email alerts
|

Is suicide mortality associated with neighbourhood social fragmentation and deprivation? A Dutch register-based case-control study using individualised neighbourhoods

Abstract: Background: Neighbourhood social fragmentation and socioeconomic deprivation seem to be associated with suicide mortality. However, results are inconclusive, which might be because dynamics in the social context are not well-represented by administratively bounded neighbourhoods at baseline. We used individualized neighbourhoods to examine associations between suicide mortality, social fragmentation, and deprivation for the total population as well as by sex and age group.Methods: Using a nested case-control d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 37 publications
3
22
1
Order By: Relevance
“…Concerning gender differences, previous studies from Australia, Scotland, and USA reported that male rural residents were at higher risk but females were not [ 10 , 16 , 20 ]. On the other hand, in the Netherland, Portugal, South Korea, and Taiwan both male and female rural residents were shown to be at higher risk [ 4 , 5 , 13 , 21 ]. Furthermore, findings have not been consistent on rural–urban differences in area suicide risk by age in previous studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning gender differences, previous studies from Australia, Scotland, and USA reported that male rural residents were at higher risk but females were not [ 10 , 16 , 20 ]. On the other hand, in the Netherland, Portugal, South Korea, and Taiwan both male and female rural residents were shown to be at higher risk [ 4 , 5 , 13 , 21 ]. Furthermore, findings have not been consistent on rural–urban differences in area suicide risk by age in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, findings have not been consistent on rural–urban differences in area suicide risk by age in previous studies. Ecological studies in the Netherland, South Korea and Taiwan showed that, regardless of age, suicide risk tended to be higher in rural areas than in urban areas [ 4 , 13 , 21 ]. On the other hand, researches carried out in Austria, Denmark, New Zealand, and the UK found that rural–urban differences in suicide risk varied by age [ 14 , 15 , 18 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Living in neighbourhoods characterised by high levels of deprivation and distrust of neighbours may be linked to suicidal thoughts and attempts through entrapment or defeat, consistent with the arrested flight, 30 cry of pain, 31 Schematic Appraisal Model of Suicide, 3 and the Integrated Motivational-Volitional Model of suicidal behaviour. 32,33 These models suggest that individuals who feel trapped by external circumstances may exhibit suicidal thoughts as they fail to find a way to escape their problems.…”
Section: Meaning Of Findingsmentioning
confidence: 99%
“…9,10 Recent findings from the Netherlands suggest associations may be more complex, with differences observed in potential influences of social fragmentation by gender and according to individual-level characteristics. 11 European Union (EU) membership referendum Previously, area-level rates of abstention from voting in the general election have been used as a measure of social fragmentation. 9 However, recent political events in the UK provide another potential measure of anomie.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Recent findings from the Netherlands suggest associations may be more complex, with differences observed in potential influences of social fragmentation by gender and according to individual-level characteristics. 11…”
Section: Introductionmentioning
confidence: 99%